Changes in soil chemical composition due to the influence of seawater and its effect on geotechnical investigations - Widiarso Dian Agus; Qadaryati Nurakhmi; Winarno Tri (E3S Web of Conferences)
North coast area of Semarang affected by the effect of seawater intrusion due to excessive groundwater pumping and seawater level rise, which impacted to characteristics of sediment and even the environment. The interaction between seawater and sediment can accelerate the compressibility process in sediments of areas in Semarang, resulting in land subsidence, as mentioned in previous studies mentioned. This research aimed to observe the influence of seawater intrusion on physical and chemical of sediment’s characteristics in north coastal area of Semarang. Sediment samples (obtained by drilling) and seawater samples are collected from 4 locations in Tambakharjo area, West Semarang. The sediment samples analyzed using XRD, whereas the seawater samples area tested using water chemistry test. The results of both tests are used to model the interaction between seawater and sediments, which is equilibrium modeling using Phreeqc 3.4. The modeling reveals the volume reduction in sediment, due to tendency of montmorillonite to release SiO2 in seawater. The interaction between sediment and seawater shows a change in montmorillonite to illite under the same conditions. This research convey that chemical composition is important to be considered in geotechnical investigation, alongside the physical properties of the lithology in usual.